Improving Diagnostic Safety by minimizing errors in Preanalytical Phase of Laboratory Testing Process - Rahman, Tahmina; Saha, Debashish; Ahmed, Rezina (Pulse, 2025)
The role of laboratory medicine is indispensable for the healthcare industry. Laboratory Services is a rapidly expanding field which contributes significantly 60–70% of clinical decisions regarding hospitalization, discharge, and medications of patients. Total laboratory testing is a cyclical process which is divided into three phases: preanalytical, analytical and postanalytical phase. The pre-analytical phase is a complex process and performed outside the laboratory. Available evidence demonstrates that the most common errors occur in the pre-analytical phase (46–68.2% of total errors). User’s feedback was collected proactively to find the gaps in the exiting process. Retrospective data was collected from February to July 2023, and it was evident that average sample rejection rate was significantly higher 2.56%, wrong investigation order error was 1.65% and sample transportation time was prolonged (average 160 minutes for inpatient and 79 min for outpatient department) in Evercare hospital Dhaka. Therefore, Laboratory stakeholders and senior leaders of Evercare hospital Dhaka decided to start hospital wide quality improvement project. The objective of this study is to identify the gaps in the preanalytical phase of diagnostic services. It was aimed to minimize the errors by developing and implementing effective quality initiatives and was targeted to decrease sample rejection rate below 2%, reduce wrong investigation input rate below 1% and to maintain IPD sample transportation TAT within 120 minutes and OPD sample transportation TAT within 60 minutes. After implementing multiple effective quality initiatives EHD successfully achieved the target and reduced sample rejection rate 1.5%, reduced investigation order error rate 0.8% and maintained sample transportation TAT for IPD 119.9 minutes and for OPD 59.2 minutes. Pulse Volume 16, Issue 2 2024, P: 19-26